Vaccination against hepatitis B: a review study - Telma Maria Evangelista Araújo; Samya Raquel Soares Dias; Vanessa Cavalcante Oliveira; Evellyn Stefanne Bastos Marques; Karinna Alves Amorim de Sousa (Universidad de Alicante, 2017)
The precise knowledge of the hepatitis B vaccination coverage is a key element for the epidemiological surveillance and interruption of the infection transmission chain. The objective of that study is to analyze the accession and the vaccination status against hepatitis B in the general population. It is an integrative literature review. They sought for articles in databases of the Virtual Health Library (VHL) - Nursing and Scientific Electronic Library Online (SciELO). Articles published in Portuguese, available online in full text and published from 2005 to 2013. At the end, 17 of the selected articles to review were included. A low vaccination coverage ranging from 14% to 99% between the groups was found. The main factors related to non- accession to vaccination were: not to like needle, to be treated for HIV, low income, lack of knowledge about the vaccines, among others. We conclude that the immunization coverage for hepatitis B is below of the recommended by the Brazilian Department of Health. In this sense, it is suggested greater role of the Family Health Strategy, in the target population of the vaccine, especially schoolchildren, and increase in permanent education health professionals.